2022
DOI: 10.1007/s41969-022-00164-1
|View full text |Cite
|
Sign up to set email alerts
|

Hyperosmolar hyperglycemic state in children: case report and review of the literature

Abstract: Hyperosmolar hyperglycemic state (HHS) is a rare complication in children and a life-threatening emergency that presents with a significant increase in blood sugar and hyperosmolarity with or without low ketosis. This study reports the case of a 9-year-old boy with severe HHS due to type 1 diabetes. The patient’s initial serum glucose level was 1600; however, he was discharged in a stable condition. The patient presented many of the known complications of HHS, including decreased level of consciousness, hypovo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…The diagnosis of hyperosmolar hyperglycemic state (HHS) in this patient can be excluded; at the presentation, the patient might be in hyperosmolar DKA due to hyper-glycemia with a random blood glucose of >600 mg/dL on the first day of hospitalization and Kussmaul respiration [26].…”
Section: Discussionmentioning
confidence: 97%
“…The diagnosis of hyperosmolar hyperglycemic state (HHS) in this patient can be excluded; at the presentation, the patient might be in hyperosmolar DKA due to hyper-glycemia with a random blood glucose of >600 mg/dL on the first day of hospitalization and Kussmaul respiration [26].…”
Section: Discussionmentioning
confidence: 97%
“…However, recent literature suggests an increasing incidence of HHS in younger, non-obese, and insulin-dependent diabetic patients. Male predominance, a poor social health network, and a positive family history of type 2 diabetes have been reported as risk factors [10]. The ingestion of large volumes of sugar-rich fluids, patients on diabetogenic medications including long-term systemic steroids, L-asparaginase, tacrolimus, growth hormone, and atypical antipsychotics, in addition to cystic fibrosis, have been identified as tangible triggers of HHS in some patients [11,12].…”
Section: Review Of Hhs and Dkamentioning
confidence: 99%
“…In DKA, the catabolic mechanism leads to an elevation in ketone bodies composed of acetone, acetoacetic acid, and beta-3-hydroxybutyrate, whereas HHS lacks significant ketoacidosis. The relatively longer period of symptomatic hyperglycemia in HHS produces an extracellular osmotic gradient, shifting fluids out of the cells and precipitating osmotic diuresis; coupled with poor fluid intake, there is an exacerbation of the negative fluid balance, resulting in extreme dehydration and severe hyperosmolar hyperglycemia without significant ketoacidosis [10]. This represents the main distinguishing difference between HHS and DKA.…”
Section: Review Of Hhs and Dkamentioning
confidence: 99%
“…They have tried to investigate how to make the diagnosis and also they have recommended treatment of this condition among children (Ng & Edge, 2017). Iraj Shahramian and his coworkers have shown that HHS is a rare complication in children with DM that shows itself with a triad: hyperglycaemia, typically greater than 600 mg/dl; hyperosmolality, serum osmolality greater than 330 mOsm/l; and mild metabolic acidosis; pH greater than 7.2; which is a life-threatening emergency with a mortality rate of 10-50% (Shahramian et al, 2022). Haralampos J. Milionis and Moses S. Elisaf have provided an outline of the diagnostic approach of patients with manifestations of HHS and discuss the contemporary therapeutic recommendations.…”
Section: Literature Reviewmentioning
confidence: 99%